The Contestation of the Communication System of the Government and the Community: A Case Study of the Development of Lon Malang Coastal Tourist Destination, Sampang Regency, Madura - Handaka, Tatag; Cholil, Ahmad (Universitas Negeri Semarang, 2023)
The purpose of this study was to identify the contestation of the village government communication system and the community communication system. The theory used was the Organizational Information Theory by Karl Weick. This study used a case study method. The results of this study showed that the village government faced the problem of suboptimal coastal management. The beach was only used as an area for sand mining. The village government then stipulated regulations in the form of developing the beach as a tourist destination. The regulations produced by the village government were rejected by the community. The community objected to this regulation because tourist destinations have the potential to create immoral places. The beach will be a place for young people to date. Tourist destinations were also not in accordance with the sociocultural environment of the community, in which there were many Islamic boarding schools around. The community wanted the tourist destination to be closed and the village government still wanted to continue the development of the tourist destination. The communication system of the village government and the community experienced a contestation in the development of Lon Malang beach as a tourist destination. The contestation on the communication system between the village government and the community continued onto the macrosystem (DPRD and regent government). The macrosystem mediated the communication system between the village government and the community. The macrosystem mediation resulted in an agreement whereby the village government was willing to fulfill some of the community's demands, and the village government was then able to develop Lon Malang Beach as a tourist destination until now.